2010
DOI: 10.1021/jp104760b
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Tunneling Transport in Molecular Junctions

Abstract: Using saturated alkyl chain series with a dithiol anchor group, we systematically examined the intrinsic charge transport of single-molecule junctions in an electromigrated nanogap electrode. The saturated alkyl molecular system constitutes an important control series in molecular transport experiments to corroborate valid molecular junctions, because molecular energy levels remain nearly unchanged with molecular length, and the transport mechanism has been unambiguously established. Inelastic electron tunneli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
60
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 39 publications
12
60
0
1
Order By: Relevance
“…The charge transport mechanism of a molecular junction can be revealed by the characteristic temperature [85][86][87] and length dependences. [87][88][89] Therefore, the measurements of temperature-and length-variable transport for the molecular junction are necessary to examine the charge transport mechanism.…”
Section: Temperature-and Length-variable Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…The charge transport mechanism of a molecular junction can be revealed by the characteristic temperature [85][86][87] and length dependences. [87][88][89] Therefore, the measurements of temperature-and length-variable transport for the molecular junction are necessary to examine the charge transport mechanism.…”
Section: Temperature-and Length-variable Transportmentioning
confidence: 99%
“…[87][88][89] Therefore, the measurements of temperature-and length-variable transport for the molecular junction are necessary to examine the charge transport mechanism. In particular, two distinct transport mechanisms have been extensively discussed in the literature: [ 2 , 5 , 6 , 8 , 85-90 ] coherent transport via tunneling or superexchange and incoherent thermally This procedure eliminates the current reduction caused by the extra tunneling gap in the STM setup.…”
Section: Temperature-and Length-variable Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…The current consensus in the field of molecular electronics is that charge transport in SAMs of insulating organic molecules proceeds via non-resonant, through-bond tunneling. 20,23,34,42,[57][58][59][60][61][62][63][64] We 19,21-23 and others [66][67][68] have previously reported that J through SAMs of nalkanethiols is approximately log-normally distributed (albeit often with long, asymmetrical tails and significant outliers), rather than normally distributed, and have suggested that variations from junction to junction in thickness and in the number or type of defects in the SAM and electrodes would lead to a normal distribution in the effective thickness, d, of the SAM. 19,[21][22][23]66,69 Since J is exponentially dependent on a normally distributed parameter (eq.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is reasonable to neglect electronphonon coupling in the molecular Hamiltonian because (a) molecules 1-4 have short chain length (<2.2 nm) and large injection gaps (>1.2 V) resulting in a small Landauer-Büttiker tunneling time (∼ 1 fs) [34,35], and (b) experimental studies show that the conductance change caused by inelastic effects due to molecular vibrations is very small (< 1%) under off-resonant conditions [36], and no significant variations of tunneling current caused by vibrationally induced decoherence appear at (2) is benzene with a para-(meta-) connection forming the two leads; molecule 3 (4) is davidene (PAM) with a para-connection. Molecule 3 and 4 contain four identical building blocks, indicated by the dashed lines, based on the structure of molecule 2, which offers two paths R1 and R2 with different length.…”
mentioning
confidence: 99%